Dynamic adjustment of emission from both singlets and triplets: the role of excited state conformation relaxation and charge transfer in phenothiazine derivates - Qiu, Weidong; Cai, Xinyi; Li, Mengke; Wang, Liangying; He, Yanmei; Xie, Wentao; Chen, Zijian; Liu, Ming; Su, Shi-Jian (Journal of materials chemistry. C, Materials for optical and electronic devices, 2021)
Luminescence behaviors in organic emitters are influenced greatly by the molecular conformation. However, the current research on room-temperature phosphorescence (RTP) mainly focuses on fixed molecular conformation, such as that in single crystals and rigid hosts. Herein, by linking the phenothiazine moiety with nitrogen heterocycles, we constructed four phenothiazine derivates having planar structure in the ground state. In the excited state, a large conformation relaxation occurs to give a dynamically tunable fluorescence and phosphorescence by the extent of the intramolecular charge transfer (ICT). In systems with a reduced ICT character, multiple emissions consisting of fluorescence and phosphorescence were observed and a white light emission was obtained in the amorphous film state. When increasing the ICT, strong spin mixing between the singlet and triplet occurs in the twisted intramolecular charge transfer (TICT) state, which is favorable for a short triplet lifetime. The emission of the thermally activated delayed fluorescence (TADF) or short RTP depends on the allowance or forbidden of fluorescence in the twisted excited state conformation. This work demonstrates the adjustment of the singlet and triplet emission behaviors through controlling the extent of TICT and provides an insight into the relationship between the molecular conformation and triplet exciton dynamics for future applications. Dynamic adjustment of emission behaviours by controlling the extent of twisted intramolecular charge transfer character in excited state.